Pengaruh Pemeriksaan Pajak Sanksi Perpajakan Dan Motivasi Wajib Pajak Terhadap Penggunaan Jasa Konsultan Pajak (Studi Empiris Pada KPP Pratama Kota Depok Tahun 2022) - Yulistio Azis Abdullah Azis; Moh Yuddy Yudawirawan (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
This study aims to provide empirical evidence of the effect of tax audits, tax sanctions and taxpayer motivation on the use of tax consultant services in the work area of the Tax Service Office (KPP) Pratama Depok Sawangan partially and simultaneously. This research is a type of quantitative descriptive research using primary data sources, namely questionnaires. The population in this study were registered individual taxpayers and then formulated through the slovin formula, 100 respondents were obtained as samples. The sample was taken using a non-probability sampling technique, then the results of the respondents' answers would be analyzed using multiple linear regression analysis techniques with the help of SPSS version 25 software. The results of the study show that tax audits, tax sanctions and taxpayer motivations together have an effect on the use of tax consultant services. Then partially found that tax audits and tax sanctions affect the use of tax consultant services. While the motivation of taxpayers does not affect the use of tax consultant services partially.